Analysis of Potassium (K) and Calcium (Ca) in Durian Seeds (Durio Zibethinus Murr) - Fahira, Gita; Said, Irwan (Universitas Tadulako, 2023)
Durian seeds are one of the wastes from durian fruit that has not been optimally utilized due to the community's lack of knowledge and creativity regarding the processing of waste into food that has economic value. This reduces the accumulation of durian seed waste that can pollute the surrounding environment. Durian seeds benefit from being used as food because they are rich in minerals, especially potassium and calcium. This study aims to determine the levels of potassium and calcium contained in durian seeds. Determination of potassium and calcium levels using atomic absorption spectrophotometer (SSA). Potassium levels were analyzed at a wavelength of 766.8 nm, and calcium was investigated at 423 nm. Before the potassium and calcium levels were determined, the moisture content and ash content were first defined in the sample. The results of the analysis of moisture in the sample obtained 2.182 % and ash content of 12.633 %. Further analysis of potassium obtained average results for potassium of 612.605 mg / 100 g and an average for calcium of 15.555 mg / 100 g. The results of this study are expected to be a source of information about potassium and calcium levels in durian seeds. They can be further utilised as an alternative food based on durian seeds, especially in the Parigi Moutong area, Central Sulawesi.